Interkingdom ecological networks between plants and fungi drive soil multifunctionality across arid inland river basin - Yin Wang; Jianming Wang; Yicheng He; Mengjun Qu; Weilin Zhu; Yujie Xue; Jingwen Li (Molecular Ecology, 2023)
Despite the known collective contribution of above‐ (plants) and below‐ground (soil fungi) biodiversity on multiple soil functions, how the associations among plant and fungal communities regulate soil multifunctionality (SMF) differentially remains unknown. Here, plant communities were investigated at 81 plots across a typical arid inland river basin, within which associated soil fungal communities and seven soil functions (nutrients storage and biological activity) were measured in surface (0–15 cm) and subsurface soil (15–30 cm). We evaluated the relative importance of species richness and biotic associations (reflected by network complexity) on SMF. Our results demonstrated that plant species richness and plant–fungus network complexity promoted SMF in surface and subsurface soil. SMF in two soil layers was mainly determined by plant–fungus network complexity, mean groundwater depth and soil variables, among which plant–fungus network complexity played a crucial role. Plant–fungus network complexity had stronger effects on SMF in surface soil than in subsurface soil. We present evidence that plant–fungus network complexity surpassed plant‐fungal species richness in determining SMF in surface and subsurface soil. Moreover, plant–fungal species richness could not directly affect SMF. Greater plant–fungal species richness indirectly promoted SMF since they ensured greater plant–fungal associations. Collectively, we concluded that interkingdom networks between plants and fungi drive SMF even in different soil layers. Our findings enhanced our knowledge of the underlying mechanisms that above‐ and below‐ground associations promote SMF in arid inland river basins. Future study should place more emphasis on the associations among plant and microbial communities in protecting soil functions under global changes.